The Untold Stories: Women on the Front-Lines of Environmental Regulation. (2nd January 2023) - Rinfret, Sara R.
Abstract: The interactions and relationships between front-line regulators and the regulated impact the implementation of environmental policy. Much of the existing research to date investigates the regulatory enforcement styles of regulators or the compliance motivations of firms. It is equally important to consider the role of women and their experiences as front-line workers. This qualitative research is one of the first to provide insight into the untold stories of women on the front-lines of environmental regulation. Through an examination of original interview data from 25 environmental regulators with the Danish Environmental Protection Agency (DEPA) and Montana Department of Environmental Quality (MT DEQ), the findings suggest steps must be taken to ensure the voices of women on the front-lines of environmental regulation are no longer overlooked. Instead, we recognize how their day-to-day experiences impact our understanding of the implementation of environmental regulations.